(untitled) (RIAF. International Journal of Physical Activity, 2026)
The inclusion of students with attention deficit hyperactivity disorder (ADHD) in Physical Education classes represents an educational challenge due to difficulties associated with behavior, attention deficits, limitations in behavioral self-regulation, and social interaction. The general objective of this study was to evaluate the effectiveness of an adapted exercise system based on traditional Ecuadorian games as an inclusive didactic strategy to improve participation, social integration, and self-regulation of students with ADHD in Physical Education. The study followed a mixed-methods approach and adopted a quasi-experimental design with pretest and posttest measurements, applied to a non-probabilistic, purposive sample consisting of seven students with a confirmed diagnosis of ADHD enrolled in the tenth year of Basic Education at an educational institution located in the Ecuadorian Amazon region. The intervention was carried out over eight weeks and included quantitative and qualitative instruments such as inclusion assessment scales, questionnaires, observation checklists, and teacher interviews. The exercise system was validated through expert judgment using the Delphi method. The results showed improvements in the motor (M = 3.64) and social (M = 3.56) dimensions, as well as progress in sustained attention and self-regulation, reflected in a reduction of impulsive behaviors. Expert validation reached an excellent rating (M = 4.98). It is concluded that the exercise system constitutes an effective and feasible pedagogical